An evolutionary-dynamic approach to strategy: beyond the attractiveness of markets and distinctive resources - Olavarrieta, Sergio A.; Friedmann, Roberto (Estudios de Administración, 1996)
The two most relevant strategy approaches present in the strategic management literature are: the market attractiveness, or Porter’s approach, and the resource-based view of the firm. Recently, however, a new strategy approach has emerged in the strategy literature. This approach, called "evolutionary approach to strategy", emphasizes the dynamic aspects of competition and highlights the role of organizational learning, market orientation, and innovativeness for developing competitive advantages. The present article examines the foundations of the evolutionary approach to strategy and compares it with the other two dominant strategic perspectives. The article also provides a discussion of the implications for business practice and future research in the field of this new- theoretical strategic perspective.